2021
DOI: 10.3390/polym13081188
|View full text |Cite
|
Sign up to set email alerts
|

Use of Extended Cover Factor Theory in UV Protection of Woven Fabric

Abstract: The paper presents an extension of existed cover factor theory more suitable for the evaluation of light penetration through a net woven fabrics structure. It also introduces a new simplified model of predicting the ultraviolet (UV) protective properties of woven fabrics assuming that the coefficient of reflection (KR), transmission (KT), and absorption (KA) of constitutive yarns are known. Since usually they are not, the procedure of preparation of simulation of proper woven fabric samples without interlacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several studies have demonstrated the UPF of standard clothing tends to be influenced by fiber type, color, and construction. The cover factor is determined by the tightness of the weave or how close the fibers are drawn together during textile construction and is considered one of the most important factors in determining the UPF of routine textiles [ 20 , 21 ]. For the average consumer shopping for clothing that may offer added UV protection, the store the garment is purchased from, the style of the garment, cost, color, and fiber composition are the features readily apparent for consumers to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the UPF of standard clothing tends to be influenced by fiber type, color, and construction. The cover factor is determined by the tightness of the weave or how close the fibers are drawn together during textile construction and is considered one of the most important factors in determining the UPF of routine textiles [ 20 , 21 ]. For the average consumer shopping for clothing that may offer added UV protection, the store the garment is purchased from, the style of the garment, cost, color, and fiber composition are the features readily apparent for consumers to consider.…”
Section: Discussionmentioning
confidence: 99%
“…It means that in practice, cover factor is calculated independently for warp and weft yarn by the proportion of fabric area covered by those yarn, according to Equation (2): Cf = Cfwa + Cfwe − Cfwa × Cfw as Cfwa = Dwa × dwa and Cfwe = Dwe × dwe, where Dwa and Dwe are densities of warp and weft and dwa and dwe are the diameter of warp and weft yarns, respectively. The cover factor directly depends on the yarn density and the yarn count [ 26 ]. Finally, the fabric weight was obtained according to the standard ISO 3801 by measuring the textile mass per unit area.…”
Section: Methodsmentioning
confidence: 99%
“…as Cfwa = Dwa × dwa and Cfwe = Dwe × dwe, where Dwa and Dwe are densities of warp and weft and dwa and dwe are the diameter of warp and weft yarns, respectively. The cover factor directly depends on the yarn density and the yarn count [26]. Finally, the fabric weight was obtained according to the standard ISO 3801 by measuring the textile mass per unit area.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of cover factor of the fabric on different properties have been studied by some authors, like flammability [7,8], UPF protection [9,10], air permeability [11][12][13][14], moisture transport [15,16], shrinkage [17,18], light transmition [19,20] or noise absorption [21].…”
Section: Introductionmentioning
confidence: 99%